A multi-level analysis of the implementation of industrial internet of things: challenges and future prospects - Rajab, Sulaiman; Saxena, Prateek; Salonitis, Konstantinos (SSRN, 2020)
Industrial Internet of Things (IIoT) is still a new research area. The main emphasis of the IIoT literature is on identifying the challenges involved in implementation of the IIoT. This paper summarizes the literature on the barriers faced by any stakeholder aiming to adopt IIoT anywhere. After reviewing 31 empirical studies, three domains of factors have been identified, individual (skills, abilities and knowledge), institutional (organizational/management-related), and structural (technical and economic infrastructures). A total of eleven factors across the three dimensions have been extracted. The most important factors were the absence of human capital (limited individual soft and technical knowledge, skills and abilities), low information security experience leading to a high probability data leaks and high management resistance from employees and leaders. To strengthen information for successful IIoT implementation, this paper proposes the mandate of Security, Education, Training, and Awareness (SETA) initiatives for any stakeholder interested in IIoT adoption. A Causal loop diagram for the IIoT implementation is also developed and discussed in this work
Keywords: Security Education and Training Awareness; Challenges; Industrial Internet of Things